Water Conservation Related Awareness and Practices of Families Living in Lahore - Malik, Nazma; Abiodullah, Muhammad; Chaudhry, Muhammad Nawaz (Nurture, 2018)
Pakistan, is likely to face serious water shortages in near future. Increasing level of awareness of the residents for water use can play an important role to control the deteriorating trend. For this purpose, a set of 19 questions were circulated to 800 residents of five localities of Southern Lahore at random, to obtain their views and adjudge their level of awareness. The data obtained have been correlated to the segments of respondents divided by the size of houses, level of education, age groups, family size and family income size.It was found that Medium house size saves more water as compared to large house size and respondents having age between 45-55 years are more aware than respondents <25 years on practices of water conservation. Similarly, household size from 1-4 are more aware regarding water conservation Practices as compared to household size (9-12). Graduate respondents are more aware than Matric and intermediate respondents in their Level of Awareness for water conservation practices.